Collaborative Governance in Sustaining Road Infrastructure Development: Addressing Land Acquisition Challenges - Hasnaini Hawazi Harmi; Rizki Syafril (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of collaborative governance in supporting the continuation of strategic road infrastructure development, particularly in addressing land acquisition challenges involving multiple stakeholders. A qualitative descriptive approach was employed. Data were collected through interviews, observations, and document analysis, and were analyzed using the Miles and Huberman interactive model. Data validity was ensured through source triangulation. The findings indicate that the collaborative governance process has been implemented through stakeholder dialogue, coordination, trust building, commitment, shared understanding, and intermediate collaborative outcomes. However, its implementation remains suboptimal due to limited public participation in decision-making, insufficient integration of inter-organizational coordination, the absence of formal agreements among stakeholders, and persistent administrative and land ownership issues affecting the land acquisition process. The study implies that strengthening institutional coordination, expanding meaningful public participation, and establishing formal collaborative mechanisms are essential to improving the effectiveness of collaborative governance and ensuring the successful implementation of strategic infrastructure development projects.